Study and quantitative analysis of wild vegetable floral diversity available in Barisal district, Bangladesh (Asian Journal of Medical and Biological Research, 2018)
In Barisal district of Bangladesh, a market survey was carried out to document the local wild vegetables floral diversity consumed by rural people and also inhabitants of metropolitan city, compare the botanical and agronomical characteristics. A total of 100 wild vegetable species belonging to 46 families have been documented from Barisal district. Among 100 wild vegetables 65% species are ethnomedicinally important and 52% are available in the all the year round. Among the species 75% hurb, 19% climber, 4% shrub and 2% trees. Leaf is most frequently used plant parts consumed and fallow land is the important source of these wild vegetables. Among 46 plant families Amaranthaceae and Araceae were recorded as most prominent. Market potentiality proportionally correlated with taste, ethnomedicinal value and use frequency but inversely correlated with distribution area, community status. Wild vegetable floral species having ethnomedicinal value, better in taste are rare and distributed into certain remote areas because frequent consumption result fast reduction from hand reach sources. Findings of this study could provide baseline data to conserve these wild vegetables, further agronomical investigation to domesticate them for sustainable use.Asian J. Med. Biol. Res. December 2018, 4(4): 362-371